Spawning ecology of the European anchovy (Engraulis encrasicolus) in the Strait of Sicily: Linking variations of zooplankton prey, fish density, growth, and reproduction in an upwelling system - Basilone, Gualtiero; Ferreri, Rosalia; Barra, Marco; Bonanno, Angelo; Pulizzi, Maurizio; Gargano, Antonella; Fontana, Ignazio; Giacalone, Giovanni; Rumolo, Paola; Mazzola, Salvatore; Genovese, Simona; McBride, Richard; et al. (Progress in oceanography, 2020)
•Habitat differences prior and during the spawning peak affected the anchovy biology.•During the spawning peak, the habitat showed a more productive upwelling system.•Upwelling conditions were a positive driver of anchovy growth and reproduction.•Food availability during the peak of spawning affected reproductive condition.•Average Fish packing density appeared to affect both egg production and somatic growth. A 12-year time series (2005–2016) was examined to explore relationships between European anchovy density, growth, reproduction and habitat dynamics in an upwelling system. Specifically, data used for a daily egg production method were combined with oceanographic data, prey availability, as well as acoustic surveys of the anchovy stock in the Strait of Sicily, in the Central Mediterranean Sea. Variables typically used for evaluating habitat dynamics (i.e. water temperature, chlorophyll-a, zooplankton concentration, kinetic energy, mixed layer depth and upwelling index) indicated strong upwelling events during the summer, when anchovy spawns. A linear ‘principal component’ combination of environmental traits, associated with summer upwelling, was identified by step-wise regression as a driver for growth (length at the end of the first year; L1), reproductive investment (gonad-somatic index; GSI), as well as egg production (daily specific fecundity; DSF). These relationships are consistent with direct energy flow from the environment to both somatic growth and reproductive output, indicating an income breeding strategy by anchovy (i.e. surplus energy acquired during the summer breeding season is used directly for reproductive growth). Step-wise regression also identified three additional relationships: (1) a density-dependent mechanism reducing growth (L1) and fecundity (DSF) at higher fish densities; (2) higher fish condition (Kn) positively affecting growth (L1); (3) higher prey availability (mesozooplankton concentration) positively affecting GSI. This time series and approach are promising for exploring the abiotic and biotic mechanisms setting year class strength in advance of recruitment to the fishery.